2019
DOI: 10.3390/en12132487
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Capacity Characteristics of Composite Bucket Foundation Under Torque Loading

Abstract: The composite bucket foundation for offshore wind turbine bears the vertical load from not only the superstructure and the horizontal load, caused by wind and wave, but also from the torque load caused by rotating structures, such as blades. Based on layered soil foundation, the influence of the skirt height, the friction coefficient between soil and bucket foundation and the diameter of the bucket foundation on the stress of the bucket skirt under the torque load are studied in this paper. Moreover, the envel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…𝑃 𝑢 < 𝑄 𝑎𝑙𝑙 (13) The variable allowable bearing capacity, Qall (kN), while SF represents the safety factor, has a value of 2.5. Lastly, the axial force that results from the factored load Pu (kN).…”
Section: Axial Bearing Capacitymentioning
confidence: 99%
“…𝑃 𝑢 < 𝑄 𝑎𝑙𝑙 (13) The variable allowable bearing capacity, Qall (kN), while SF represents the safety factor, has a value of 2.5. Lastly, the axial force that results from the factored load Pu (kN).…”
Section: Axial Bearing Capacitymentioning
confidence: 99%
“…Numerical modeling is a common method for analyzing the bearing capacity of foundations [36][37][38], which has the advantages of an unlimited number of test samples and a high flexibility of the simulation scheme.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The results indicated that increasing the depth of penetration of both the foundation pile and bucket effectively enhanced the structure resistance of overturning. Wang et al [5] highlighted that, relative to sandy soil, the enhancement in the overall bearing capacity of the structure is more pronounced in soft clay with a pile-bucket composite foundation in a comparative study involving a single-pile foundation, bucket-shaped foundation, and pile-bucket composite foundation; Sun et al [6] asserted that the diameter of the bucket has the greatest impact on the load-bearing performance of the pile-bucket composite foundation with an increase in bucket diameter proving to be an effective means of enhancing structural load-bearing capacity; Huang et al [7] studied the sharing of the load by different parts of the foundation and the failure mode under vertical loading, concluding that composite foundation can effectively improve load-bearing capacity; Zhou et al [8] proposed a theoretical formula for the horizontal load-bearing capacity of a pilebucket composite foundation considering varying numbers of piles based on the ultimate equilibrium method; Wang et al [9] studied the load-bearing capacity degradation patterns of the pile-bucket composite foundations under static and cyclic loading, indicating that, compared to bucket height, an increase in bucket diameter more significantly improved the load-bearing capacity of the foundation; Chen et al [10] investigated the response of the pile-bucket composite foundation under static and dynamic loads, demonstrating that the composite foundation can reduce the depth of the pile penetration and effectively decrease the rotation angle and horizontal displacement of the foundation; and Liu et al [11] conducted modal analysis on a pile-bucket composite foundation with ABAQUS software and highlighted optimal pile-bucket diameter ratios and bucket skirt height. Chen et al [12] found that, compared with single-pile foundations, the pile-bucket composite foundation significantly reduced the seismic response of offshore wind turbines (OWTs).…”
Section: Introductionmentioning
confidence: 99%